Sistem Pengelolaan Lingkungan Dan Upaya Penanggulangan Sampah Di Kelurahan Mangkio Baru Kabupaten Banggai - Susana Asgun; Zelvy Laga; Ishak Ishak (Universitas Pahlawan Tuanku Tambusai, 2025)
The research objectives regarding waste issues never stop being discussed, because they are related to the lifestyle and culture of the community itself. Banggai Regency is one of the regencies with the nickname Water City, which is experiencing population and economic growth which is sufficient to trigger an increase in service, industrial, business, educational activities and so on in the Banggai Regency area, which will trigger an increase in the production of waste or community waste. Banggai Regency is experiencing waste management problems, namely the problem of transporting waste, based on data that the amount of available transport infrastructure is only produced by market traders such as vegetables and rotting fruit which are temporarily collected, then after the market is closed the waste is thrown into TPS (Containers) without any proper processing. So a lot of rubbish is scattered on the road, causing the market environment to look dirty and smell bad. This research is a type of descriptive research. This research is a type of descriptive research using frequency distribution data analysis methods by analyzing the waste management system in Mangkio Baru Village. The results of the research show that waste management in Banggai Regency is not good enough, several factors that influence the waste management system in Mangkio Baru Subdistrict are still experiencing problems, namely the cultural attitudes and behavior of the community, the accumulation and characteristics of waste, as well as the means of collecting, transporting, managing and final disposal of waste (TPA). For port locations where waste produced by traveling people is directly disposed of at TPS and at sea. The results of this research should be that waste must be properly processed so that people who travel will no longer throw rubbish into the sea, so that the sea will be clean. able to transport waste generation of 204 m³/day, Banggai Regency sanitation service, (2024) whereas based on calculations that waste generation in 2024 is 410 m³/day based on the results of the 2021 survey on the current population of Banggai Regency, which is 376,808 people, Banggai Regency BPS in figures, (2023) means that 51% of waste is not transported to the landfill. The increasing production of waste without a proper processing system is the reason for not creating good and clean environmental management.